Cuadro de ansiedad en una persona privada de libertad que ingresa a la cárcel por primera vez - Cundulli Lisintuña, Carlos Aníbal (2020)
People deprived of liberty in Ecuador each time enter an alarming number, the spaces where they have to serve their sentence is totally deteriorated, reduced and must live with people who have committed all kinds of serious crimes such as death, rape, theft arming, trafficking and consumption of illicit substances, facing this situation is where a person who enters a prison for the first time must remain. This case study is directly related to the line and research subline of the clinical psychology clinic: diagnosis and prevention, behavioral disorder and its impact on the teaching-learning process, in turn in order to reduce anxiety levels in a person who enters jail for the first time. The work focuses specifically on the mental health of the person, the types of anxiety can be known, since the normal, pathological anxiety and a disorder are totally different and their treatment varies completely according to the need presented, the deprivation of the freedom to a person has an objective it will be known what rights will be restricted for inmates. In order to carry out the case study, the different techniques used as clinical interviews, psychometric tests that are used for the collection of information will be detailed, this in turn allows obtaining both psychological tests and clinical observation in the cognitive part, affective, thinking, social behavior thus establishing a diagnosis according to DSM-5 F41.1 (300.02) to apply a therapy with the TREC model, using the different techniques recommended by the author of ABC therapy, is applied the twelve steps established in the model and finally reaching the conclusion and recommendation to follow daily.